2022
DOI: 10.3389/fnana.2022.813369
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterisation of the Whale Retina

Abstract: The eye of the largest adult mammal in the world, the whale, offers a unique opportunity to study the evolution of the visual system and its adaptation to aquatic environments. However, the difficulties in obtaining cetacean samples mean these animals have been poorly studied. Thus, the aim of this study was to characterise the different neurons and glial cells in the whale retina by immunohistochemistry using a range of molecular markers. The whale retinal neurons were analysed using different antibodies, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Whale primary and immortalized Müller cells were also characterized immunocytochemically using the Müller cells markers GS ( Mack et al, 1998 ) and GFAP ( Lewis et al, 1988 ), the neural marker β-III-Tubulin ( Jiang et al, 2015 ) and the marker of dedifferentiation or a fibroblastic phenotype, α-SMA ( Darby et al, 1990 ) ( Figures 8 , 9 ). Parallel studies demonstrated that these specific markers are present in the Müller glia of the whale retina ( Ruzafa et al, 2022 ). GS is the main enzyme involved in transmitter recycling in Müller cells, and it is downregulated in immortalized Müller cells after 10 passages.…”
Section: Discussionmentioning
confidence: 90%
“…Whale primary and immortalized Müller cells were also characterized immunocytochemically using the Müller cells markers GS ( Mack et al, 1998 ) and GFAP ( Lewis et al, 1988 ), the neural marker β-III-Tubulin ( Jiang et al, 2015 ) and the marker of dedifferentiation or a fibroblastic phenotype, α-SMA ( Darby et al, 1990 ) ( Figures 8 , 9 ). Parallel studies demonstrated that these specific markers are present in the Müller glia of the whale retina ( Ruzafa et al, 2022 ). GS is the main enzyme involved in transmitter recycling in Müller cells, and it is downregulated in immortalized Müller cells after 10 passages.…”
Section: Discussionmentioning
confidence: 90%
“…Calretinin-positive ganglion cells are present as different morphological subtypes in numerous species; in the mouse, about 85% of all ganglion cells showed a positive signal [44]. In Mysticeti, a similar pattern could be seen with the intense staining of horizontal and amacrine cells; however, no positive signal was found in the ganglion cell layer [50].…”
Section: Immunohistochemistrymentioning
confidence: 94%
“…Intrinsically photosensitive retinal ganglion cells also have been identified in other mammals such as the tree shrew (Johnson et al, 2019), whale (Ruzafa et al, 2022), and primates (Liao et al, 2016;Esquiva et al, 2017;Hannibal et al, 2017;Mure et al, 2019;Nasir-Ahmad et al, 2019). Adult human eyes contain about 4,000-7,500 cells immunolabeled with anti-melanopsin antisera (see Table 1).…”
Section: Rodent and Primate Intrinsically Photosensitive Retinal Gang...mentioning
confidence: 99%